2013
DOI: 10.7589/2011-07-204
|View full text |Cite
|
Sign up to set email alerts
|

Serologic, Molecular, and Pathologic Survey of Toxoplasma Gondii Infection in Free-Ranging Red Foxes (Vulpes Vulpes) in Central Italy

Abstract: ABSTRACT:We tested 191 sera of red foxes (Vulpes vulpes; 78 females and 113 males) for antibodies to Toxoplasma gondii using an indirect immunofluorescent test. Tissue samples of myocardium, lymph nodes, and brains from antibody-positive animals were tested for T. gondii DNA using specific PCR and processed for histopathology and immunohistochemistry (IHC) to detect T. gondii antigen. Of 192 (53.4%) antibody-positive animals, eight were positive by PCR on myocardium and one on brain. All DNA extracts were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Genotyping has previously been carried out in Italy on T gondii DNA from both domestic and sylvatic animals, indicating the occurrence of strictly clonal genotypes in goats 35 and cats, and mixed types detected in free-ranging waterfowl 36 and foxes. 37 These results are in agreement with the hypothesis of two distinct cycles of T gondii in domestic and sylvatic environments. 38 Eleven cats were positive for G duodenalis DNA, with an overall prevalence of 7.5%, which is in agreement with Paoletti et al 18 Genotyping yielded nine assemblages, with F the most frequent in cats and C the most common in dogs.…”
supporting
confidence: 89%
“…Genotyping has previously been carried out in Italy on T gondii DNA from both domestic and sylvatic animals, indicating the occurrence of strictly clonal genotypes in goats 35 and cats, and mixed types detected in free-ranging waterfowl 36 and foxes. 37 These results are in agreement with the hypothesis of two distinct cycles of T gondii in domestic and sylvatic environments. 38 Eleven cats were positive for G duodenalis DNA, with an overall prevalence of 7.5%, which is in agreement with Paoletti et al 18 Genotyping yielded nine assemblages, with F the most frequent in cats and C the most common in dogs.…”
supporting
confidence: 89%
“…In Spain, antibodies to N. caninum were demonstrated by cELISA and confirmed by IFAT in 3.2% of 95 red foxes [6], similar to the presented study; also similar to this study, a high T. gondii seroprevalence (100%) was found in 123 foxes in Belgium [7]. Antibodies to T. gondii were detected by immunoblot analysis in 74.5% of 204 and 84.7% of 176 red foxes in Germany [8], and by IFAT in 53.4% of 191 foxes in Italy [9]. Higher T. gondii prevalence compared to N. caninum was detected also in other countries.…”
Section: Discussionsupporting
confidence: 91%
“…This is the first report of a T. gondii genotype in wild Italian ungulates. Despite having used different protocols, Verin et al (2013) demonstrated the occurrence of polymorphic strains (combination of different type I and III alleles) in red foxes (Vulpes vulpes) and Mancianti et al (2013Mancianti et al ( , 2014 detected genotypes I and III and atypical genotypes (with hints of genotype I) in goats and genotypes II and III in donkeys. Therefore, all the T. gondii genotypes appear to be present in Italy.…”
Section: Discussionmentioning
confidence: 99%